Increased Smooth Muscle Kv11.1 Channel Expression in Pulmonary Hypertension and Protective Role of Kv11.1 Channel Blocker Dofetilide - Shults, Nataliia V. (Am J Pathol, 2020)
Kv11.1 potassium channels are essential for heart repolarization. Prescription medication that blocks Kv11.1 channels lengthens the ventricular action potential and causes cardiac arrhythmias. Surprisingly little is known about the Kv11.1 channel expression and function in the lung tissue. Here we report that Kv11.1 channels were abundantly expressed in the large pulmonary arteries (PAs) of healthy lung tissues from humans and rats. Kv11.1 channel expression was increased in the lungs of humans affected by chronic obstructive pulmonary disease–associated pulmonary hypertension and in the lungs of rats with pulmonary arterial hypertension (PAH). In healthy lung tissues from humans and rats, Kv11.1 channels were confined to the large PAs. In humans with chronic obstructive pulmonary disease–associated pulmonary hypertension and in rats with PAH, Kv11.1 channels were expressed in both the large and small PAs. The increase in Kv11.1 channel expression closely followed the time-course of the development of pulmonary vascular remodeling in PAH rats. Treatment of PAH rats with dofetilide, an Kv11.1 channel blocker approved by the US Food and Drug Administration for use in the treatment of arrythmia, inhibited PAH-associated pulmonary vascular remodeling. Taken together, the findings from this study uncovered a novel role of Kv11.1 channels in lung function and their potential as new drug targets in the treatment of pulmonary hypertension. The protective effect of dofetilide raises the possibility of repurposing this antiarrhythmic drug for the treatment of patients with pulmonary hypertension.